"Being in Control of My Asthma Myself" Patient Experience of Asthma Management: A Qualitative Interpretive Description - Damilola T. Olufemi-Yusuf; Sophie Beaudoin Gabriel; Tatiana Makhinova; Lisa M. Guirguis (MDPI AG, 2018)
Asthma control can be achieved with effective and safe medication use; however, many patients are not controlled. Patients’ perceptions of asthma, asthma treatment, and pharmacist roles can impact patient outcomes. The purpose of this study was to explore patients’ experiences and patient⁻pharmacist relationships in asthma care. Qualitative Interpretive Description method guided the study. Semi-structured individual interviews were conducted with 11 patients recruited from personal contacts, pharmacies, and asthma clinics. Categories and themes were identified using inductive constant comparison. Themes indicated patients had a personalized common sense approach to asthma management, “go-to„ health care provider, and prioritized patient⁻pharmacist relationships. Patients described their illness experiences and asthma control based on personal markers similar to the common sense model of self-regulation. Patients chose a family physician, asthma specialist, respiratory therapist, or pharmacist as an expert resource for asthma management. Patient perceived pharmacists’ roles as information provider, adviser, or care provider. Pharmacists who develop a collaborative relationship with their asthma patients are better positioned to provide tailored education and self-management support. Inviting patients to share their perspective could increase patient engagement and uptake of personalised asthma action plans to achieve asthma control.